Biology and management of fruit borer, Virachola isocrates (Fab.) Infesting guava (Bangladesh Journal of Agricultural Research, 2016)
Two experiments were conducted to study the biology of guava fruit borer, Virachola isocrates (Fab.) and to evaluate the effectiveness of management practices for managing fruit borer, Virachola isocrates (Fab.) in Sharupkathi variety of guava. The biology including morphometrics of guava fruit borer were studied in the laboratory of the Department of Entomology, PSTU, Dumki, Patuakhali during May to October, 2012. Results revealed that incubation period, larval period, pupal period of this borer ranged from 8-10, 17-46, 7-33 days, respectively and total life cycle was completed within 30 to 60 days. Adult longevity ranged from 4-7 days. The average length of full grown larva was 17.45 mm, and breadth across thorax and abdomen were 3.36 and 2.80 mm, respectively. The average length of pupa was 15.90 mm, and breadth across thorax and abdomen were 3.68 and 2.89 mm, respectively. The average length of adult body was 16.90 mm, and breadth across thorax and abdomen were 3.91 and 2.94 mm, respectively. The average length of antennae was 10.35 mm. The mean length of pro-, meso and metathoracic legs was 7.55mm, 8.10mm and 10.45 mm, respectively. The metathoracic leg was longer as compared to pro and mesothorarcic legs. The length of fore wing across the upper and lower margin ranged from 16.00 mm to 18.00 mm and 11.50 mm to 12.00 mm, respectively. The length of hind wing across the upper and lower margin ranged from 10.00 mm to 11.00 mm and 8.00 mm to 9.00 mm, respectively. The breadth of fore wing across the middle ranged from 10.50-11.00 with mean breadth of 10.78 mm. Likewise, the breadth of hind wing across the middle ranged from 11.00-14.00 with mean breadth of 12.55 mm. The results on the percent infestation reduction over control revealed that package with field sanitation + collection of infested fruits + application of Superior (Chlorpyrifos + Cypermethrin) 505 EC @ 1 ml/ l water, and package consisting of field sanitation + collection of infested fruits + bagging of fruits with polythene bag gave 100 % control of the pest. These two packages may be used for the large scale cultivation of Sharupkathi variety in BangladeshBangladesh J. Agril. Res. 41(1): 41-51, March 2016